The influence of relative age on the composition of professional soccer squads - Ostapczuk, M.; Musch, J. (European Journal of Sport Science, 2013)
Children born shortly after the cut-off date applying for age grouping in minor sports profit from being able to remain for almost an additional year in their respective age group compared to those born later in the same year. A shift of the cut-off date in German youth soccer in 1997 allowed us to investigate the effect of a favourable relative age as well as the effect of a change of the cut-off date on the birth-date distribution of soccer players in the Bundesliga (Division 1), the highest professional soccer league in Germany. Both the cut-off date and the change of the cut-off date exerted a significant influence on the composition of professional senior squads. In the 1997/98 season, there was an overrepresentation of players profiting from the old cut-off date of 1 August. In the 2007/08 season, 10 years after the change of the cut-off date, there was an overrepresentation of players born shortly after the new cut-off date of 1 January. This pattern of results shows that owing to the cut-off dates applying in youth soccer, the date of birth of young players systematically influences their later professional success and career.